Homecoming: reclaiming and championing your inner child - Bradshaw, John, 1933-2016 (New York : Bantam Books, 1992)
'Three things are striking about inner child work. The speed with which people change when they do this work; thedepth og that change; and the power and creativity that result when the wounds from the past are healed.' Here, using a wealth of practical techniques, informative case histories, and unique questionnaires, Bradshaw demonstrates how your wounded inner child may be causing you pain. You will learn to gradually, safely, goback to reclaim and nurture that inner child - and literally help yourself grow up again
The problem of the wounded inner child -- How your woundedinner child contaminates your life -- How your wonderful inner child got wounded -- Reclaiming your wounded inner child -- Original pain work -- Reclaiming your infant self -- Reclaiming your toddler self -- Reclaiming your preschool self -- Reclaiming your school-age self -- Pulling yourself together: a new adolescence -- Championing your wounded inner child -- Using your adult as a new source of potency -- Giving your inner child new permissions -- Protecting your wounded inner child -- Putting corrective exercises into place -- Regeneration --The child as a universal symbol of regeneration and transformation -- The wonder child as Imago Dei -- Epilogue:'Home, Elliott, home!'.
Includes bibliographical references : pages [287-288].
Keywords: Inner child; Self-actualization (Psychology).